Logika Kreatif Inovatif dan Bid’ah Dalam Pengelolaan Pendidikan Islam di Madrasah Aliyah Miftahul Ulum Subang - Iyus Tsaury; Irawan Irawan; Rohmat Mulyana Sapdi (Yayasan Cendekia Gagayunan Indonesia, 2026)
The integration between creative and innovative logic and the concept of bid’ah within the management of Islamic education, particularly in the context of modernization. Using a qualitative approach through literature review and field research conducted at MA Miftahul Ulum Subang, the study reveals that creativity and innovation are strategic necessities for both instructional and managerial development in Islamic educational institutions in the digital era. Questionnaire data indicate that the majority of students (87–93%) positively accept technology-based innovations in Islamic education and do not perceive them as conflicting with Islamic values. Interviews with teachers and the principal show that innovation is only considered bid’ah when it interferes with ritual worship (ibadah mahdhah), whereas innovations in management, curriculum, and technology fall under the permissible domain of muamalah. The study concludes that Islamic educational management must integrate creative and innovative thinking with core Islamic principles through the framework of maqāṣid al-sharī‘ah and the classical guideline al-muḥāfaẓah ‘alā al-qadīm al-ṣāliḥ wa al-akhdzu bi al-jadīd al-aṣlaḥ. Findings provide a model for how Islamic educational institutions can modernize effectively without falling into reprehensible bid’ah.